The problems of providing operational reliability of drill string elements - Івасів, Василь Михайлович; Гриджук, Ярослав Степанович; Гриців, Василь Васильович; Юрич, Лідія Романівна (Technology audit and production reserves, 2015)
Critical review of the literature and publications towards research aimed at solving the problem of providing operational reliability of drill string (DS) are conducted in the article. The analysis concluded that no single approach to solving problems and studies that have focused primarily on the practical application of the theoretical foundations and constantly connected with results of their industrial implementation. The first priority in solving scientific and technological problems is to develop an algorithm to ensure operational DS reliability that would allow as quickly as possible to assess the actual burden and the failure risks of its elements. The second stage is improving the system of registration of actual loads acting on DC and system of their processing as well as operating time monitoring system of DC elements from the date of receipt in the drilling company and until disposal. To develop a method for assessing the risk of failure of DS elements considering the accumulated information at the design stage and directly in the process. The study can be used to improve forecasting methods and assessment of resource of DS elements.